Practical Management of Diabetes during Ramadan Fasting. - Fariduddin, M; Mahtab, H; Latif, ZA; Siddiqui, NI (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):541-546 The abstract of this article is available on the PubMed website